Electrically conductive Cu(ii)-based 1D coordination polymer with theoretical insight. Issue 43 (29th October 2020) - Islam, Sakhiul; Das, Pubali; Maiti, Saswati; Khan, Samim; Maity, Suvendu; Ghosh, Prasanta; Jana, Atish Dipankar; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : A nitro-functionalized Cu(ii )-based 1D CP generates a 3D supramolecular assembly through a novel "super-supramolecular" synthon, which exhibits electrical conductivity and reveals a Schottky diode behaviour. Abstract : A nitro-functionalized Cu(ii )-based one-dimensional coordination polymer (1D CP) [Cu(nip)(4-phpy)2 ] n (1 ) (H2 nip = 5-nitroisophthalic acid and 4-phpy = 4-phenylpyridine) was synthesized and characterized by elemental analysis, powder X-ray diffraction (PXRD) and single crystal X-ray diffraction (SCXRD). In the solid-state self-assembly of 1, two sets of weak intermolecular forces, CH⋯π interaction among the axially bound 4-phpy ligands and π⋯π interaction among bridging nip ligands from adjacent 1D coordination polymeric chains led to 3D supramolecular packing. Interestingly compound 1 exhibited electrical conductivity in the semiconducting regime and behaved as a Schottky barrier diode.